Biomimetic Shape–Color Double‐Responsive 4D Printing. Issue 9 (17th June 2019) - Wang, Jingchun; Wang, Zhenguo; Song, Zhengyi; Ren, Luquan; Liu, Qingping; Ren, Lei
Abstract: An emerging technology for producing programmable stimuli‐response materials, 4D printing, is currently confined to shape changing. A new type of 4D printing technology that produces shape–color double‐responsive materials similar to those ubiquitous in biomaterials systems, such as octopuses simultaneously altering their skin color and shape in response to environmental stimuli, is presented. Shape–color double‐responsive composites are prepared through the incorporation of shape‐memory polymer (polylactic acid) and thermochromic pigments. Using the prepared composites and a fused deposition modeling 3D printer, shape–color double‐responsive 4D printing is achieved. The influence of the process parameters and stimulus methods on the characteristics of 4D deformation and discoloration is investigated. Furthermore, by regulating the geometry, process parameters, and stimulus conditions, the speed of shape changing and color transition can be controlled simultaneously. Finally, as a proof‐of‐concept, biomimetic soft robots with shape–color dual responses, including a color‐shifting blooming flower and a camouflaging octopus, are demonstrated. Compared with previously reported 4D printing technologies, this research offers a facile method for manufacturing multiresponsive active composites. The developed shape–color double‐responsive 4D printing method is expected to be helpful for exploring the full potential of 4D printing. Abstract : Inspired by camouflage in nature, a new type of 4D printing technology is developed. It can simultaneously control the shape changing and color transition speed of thermochromic composite shape‐memory polymer by regulating the geometry, process parameters, and stimulus conditions. Biomimetic soft robots with shape–color dual responses, including a color‐shifting blooming flower and a camouflaging octopus, are demonstrated.